Vestibular neuronitis associated with an adult male COVID-19 infection: A case report - Yaser Said Cetin (Journal of the Pakistan Medical Association, 2022)
In the present era of the coronavirus 2019 (COVID-19) pandemic, it has been observed that the severe acute respiratory syndrome, coronavirus 2 (SARS-CoV-2) infection does not only affect the respiratory tract, but also triggers various neurological symptoms in one-third of patients. The most prominent of such symptoms is anosmia, which is independent of rhinologic symptoms such as nasal obstruction, discharge, and pain that cannot be otherwise explained. Vestibular neuronitis ranks third among the causes of peripheral vestibular vertigo, characterized by nausea, vomiting, and dizziness that develops within minutes or hours. Although the etiopathogenesis remains poorly known, neuronitis is generally considered to be attributable to the viral or post-viral inflammation of the vestibular branch of the eighth cranial nerve. This report presents a case of vestibular neuronitis, which is likely to be a manifestation of acute vestibular neuronitis associated with COVID-19. Keywords: Anosmia; COVID-19; COVID-19 Pandemics; Vertigo; Vestibular Neuronitis